Towards intervention development to increase the uptake of COVID‐19 vaccination among those at high risk: Outlining evidence‐based and theoretically informed future intervention content. Issue 4 (5th September 2020) - Williams, Lynn; Gallant, Allyson J.; Rasmussen, Susan; Brown Nicholls, Louise A.; Cogan, Nicola; Deakin, Karen; Young, David; Flowers, Paul
Abstract : Objectives: Development of a vaccine against COVID‐19 will be key to controlling the pandemic. We need to understand the barriers and facilitators to receiving a future COVID‐19 vaccine so that we can provide recommendations for the design of interventions aimed at maximizing public acceptance. Design: Cross‐sectional UK survey with older adults and patients with chronic respiratory disease. Methods: During the UK's early April 2020 'lockdown' period, 527 participants (311 older adults, mean age = 70.4 years; 216 chronic respiratory participants, mean age = 43.8 years) completed an online questionnaire assessing willingness to receive a COVID‐19 vaccine, perceptions of COVID‐19, and intention to receive influenza and pneumococcal vaccinations. A free text response ( n = 502) examined barriers and facilitators to uptake. The Behaviour Change Wheel informed the analysis of these responses, which were coded to the Theoretical Domains Framework (TDF). Behaviour change techniques (BCTs) were identified. Results: Eighty‐six per cent of respondents want to receive a COVID‐19 vaccine. This was positively correlated with the perception that COVID‐19 will persist over time, and negatively associated with perceiving the media to have over‐exaggerated the risk. The majority of barriers and facilitators were mapped onto the 'beliefs about consequences' TDF domain, with themes relating to personal health, health consequences to others, concerns of vaccine safety, and severity of COVID‐19. Conclusions: Willingness to receive a COVID‐19 vaccination is currently high among high‐risk individuals. Mass media interventions aimed at maximizing vaccine uptake should utilize the BCTs of information about health, emotional, social and environmental consequences, and salience of consequences.